Serbia : Investment Climate Asessment - World Bank (Washington, DC, 2013)
The objective of this Investment Climate Assessment (ICA) is to (1) provide Serbian experts in academia and in government, as well as Bank staff, with an empirical analysis of the investment climate in Serbia; and (2) to discuss policy options, based on this analysis, for creating an enabling environment conducive to private sector development, thereby increasing and maintaining enterprise productivity and profitability leading to sustainable growth. The study is part of a Bank-wide effort, managed and funded by the Investment Climate Unit of the Investment Climate Department, to analyze the effects of various characteristics of the investment climate on productivity in an international context. One of the main messages of this ICA is the need to increase investor confidence in Serbia; the ICA identifies a number of policies that, if implemented, could improve the perception of Serbian investment climate. In particular, it should be stressed that reversals in policy and lack of respect for property rights on investors that have already invested in Serbia could cause serious harm.